Molecular Identification of Snapper (Perciformes: Lutjanidae) Landed at Pondokdadap Fishing Port of Sendang Biru, Malang, Indonesia - Sapto Andriyono; Novian Aji Pradana; Laksmi Sulmartiwi; Andi Aliah Hidayani; Md. Jobaidul Alam; Adrian Damora; Ahasan Habib (Marine Science Department Diponegoro University, 2022)
Snapper is a type of demersal marine fish from the Lutjanidae family. The Lutjanidae family spread throughout the world and currently has 123 species in 21 genera, one of which is the Lutjanus genus (Miller and Thomas, 2007). To this day, the records of capture fisheries production data for snapper in Malang are still very limited to certain types. Morphological identification that has been carried out so far is still challenging to obtain accurate results because of the many similarities between the observed species or the loss of characteristics. Therefore, molecular identification is necessary to determine the types of snappers in this area and their conservation status. This study aims to determine the types of snappers using a molecular approach by Cytochrome Oxidase subunit I (COI) gene marker. Phylogenetic tree reconstruction and genetic distance calculations were performed using Mega X software through the neighbour-joining (NJ) algorithm. The results of the identification snapper based on a molecular approach with DNA barcoding revealed that the four snapper samples were L. gibbus, L. rufolineatus, L. bengalensis, and L. erythropterus. Based on the results of the compilation of the phylogenetic tree, it can be seen that the L. bengalensis sample is closely related to L. rufolineatus while L. gibbus, and L. erythropterus each form a separate clade from the two previous Lutjanus species. Based on their conservation status at the IUCN, the four species of snapper found are in the Least Concern category.